Studi Literatur Analisis Boraks pada Bakso yang Beredar di Pasar Tradisional Indonesia Menggunakan Berbagai Metode - Siti Nur Habibah; Mi’rajunnisa Mi’rajunnisa; Yulianita Pratiwi Indah Lestari (BORNEO JOURNAL OF PHARMASCIENTECH, 2022)
Borax is a chemical compound that contains the element Boron (B). The purpose of this study is to determine whether meatballs circulating in various markets in Indonesia contain borax, in what levels, and how to compare the results of the analysis with various methods based on a literature study. The design of this research is to use a literature study method which is done by studying journals about tracing borax analysis journals on meatballs using various methods. The quantitative test used alkalimetric titration test, UV-Vis spectrophotometry, and Visible spectrophotometry. The results of the organoleptic test on meatballs containing borax were pale white in color, smelled like meatballs in general but had a slight chemical smell, and tasted chewy. The flame test of 3 positive studies contained borax in the presence of a green color from the flame. Tumeric paper test from 2 positive studies contained borax with a color change on the tumeric paper from yellow to brownish red. Alkalimetric titration test from 2 positive studies contained borax with a color change at the end of the titration to pink with levels of 3.82 ppm and 0.06-5.15%. Tests with UV-Vis spectrophotometry obtained results with a wavelength of 555 nm with a linearity that is R=0.9995 and an accuracy of 96.09%-104.62%, with the highest level of 2414,375 g/mL and the lowest 129,375 g/mL. Visible spectrophotometry test obtained results with a wavelength of 620 nm, namely the meatballs before being burned with a value of 0.54 ppm.